A TV em plataforma : um estudo sobre a trajetória do Globoplay e a atuação de emissoras brasileiras de televisão aberta no campo do streaming de vídeo - Fagundes, Carolina Santos (2021)
The year 2020 marks the seventy years of Brazilian television. Throughout this period, this means of communication was able to adapt to market trends and phenomena that have dissipated throughout its seven-decade trajectory. The popularization of streaming as a model of distribution of audiovisual content is an emerging fact that has brought trials to companies in various fields, including those located in the television field, generating a clash between distribution logics and an increasingly fierce competition, which instead influence the strategies of production, distribution, promotion and consumption of audiovisual works. The clash between these logics fosters debates on issues such as the performance of advertising in streaming, technology and creativity as agents of change in the market, as well as the need to determine rules for the performance of companies that use this model in the country. For this work, we seek to analyze the performance of Brazilian television stations in the field of streaming platforms operating in Brazil, having as object of investigation Globoplay, Globo's bet for this market, in addition to observing the initiatives of broadcasters such as Record and SBT for comparative purposes. To this end, we propose the construction of the social trajectory of the platform using concepts of the Theory of Fields (Bourdieu, 1989, 1992, 1997, 2005, 2006) as field, trajectory and capitals in order to analyze the impacts of streaming technology in the Brazilian entertainment market and how television companies behave in the face of the new scenario imposed by the dynamics of this phenomenon. Thus, we could observe that the companies in the television field are important for the development of the streaming market in Brazil, so that broadcasters such as TV Globo, TV Record and SBT, find ways to combine their performance in broadcasting also with streaming, at this point, we observe that their initiatives in this model are in accordance with their traditional institutional discourses, in addition to observing that business models and marketing strategies differ with regard to the initiatives of the three Brazilian companies. Thus, by building the social trajectory of Globoplay, we also see that this is the most developed initiative and tuned to the practices common to the phenomenon of streaming and the agents already consolidated in this field, while strengthening the culture of television in this market.